A review of the combined torrefaction and densification technology as a source of renewable energy - Thandiwe Sithole; Godwell Pahla; Tebogo Mashifana; Tirivaviri Mamvura; Elena-Niculina Dragoi; Anbalagan Saravanan; Hasan Sadeghifar (Alexandria Engineering Journal, 2023)
Densification techniques allow biomass to be used in the energy mix with coal or as a direct replacement for coal as it is a renewable resource. Typically, biomass is bulky, so thermochemical methods, like torrefaction, reduce volatiles and moisture, leaving a higher composition of fixed carbon. After the torrefaction process, the torrefied biomass poses problems during handling, transportation, and storage because it consists of small (<100 μm) disintegrated particles. Densification minimizes these problems through thermal compaction which produces integrated and larger (4 mm – 200 mm diameter) solid particles. This process can be done naturally (without any additives) or by adding binders which improve the torrefied biomass’s physical, chemical, mechanical, and heating properties. This in turn reduces any costs associated with handling/transportation and storage of the biomass before it is used for energy generation. Densification increases the biomass’s energy content per unit volume thereby enabling coal substitution. Recent reviews on densification have mainly focused on the binding of coal fines, raw biomass, and some torrefied biomass. Reviews on the binding theories are also available. This current review focuses solely on the aspect of torrefied biomass densification and the factors associated with the process. Insights and recommendations for the possible application of an integrated biomass torrefaction and densification process were provided herein. In addition, the gaps in literature were identified to enable future research on the application of the process to realize innovative renewable energy production in industry.